2020
DOI: 10.1111/hepr.13511
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib in patients with unresectable hepatocellular carcinoma who do not meet the REFLECT trial eligibility criteria

Abstract: AimThis study aimed to determine the efficacy and safety of lenvatinib for patients with unresectable hepatocellular carcinoma (HCC) who did not meet REFLECT eligibility criteria (phase 3 clinical trial).MethodsIn this multicenter retrospective study, patients with unresectable HCC treated with lenvatinib between 2018 and 2019 and had adequate clinical data were included. Objective response rate, progression‐free‐survival (PFS) and safety were evaluated according to meeting or not meeting the REFLECT eligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 29 publications
3
46
0
8
Order By: Relevance
“…Many real-world studies have reported the short-term therapeutic response of lenvatinib, resulting in an ORR of 29.9-53.5%, as assessed by mRECIST [17][18][19][20][21][22][23][24], and 14-25%, as assessed by RECIST ver.1.1 [19,22,25,26]. These findings seemed to be in agreement with the results of phase 2 and 3 studies (Table 1).…”
Section: Therapeutic Response Of Lenvatinib 21 the Ojective Responssupporting
confidence: 86%
See 4 more Smart Citations
“…Many real-world studies have reported the short-term therapeutic response of lenvatinib, resulting in an ORR of 29.9-53.5%, as assessed by mRECIST [17][18][19][20][21][22][23][24], and 14-25%, as assessed by RECIST ver.1.1 [19,22,25,26]. These findings seemed to be in agreement with the results of phase 2 and 3 studies (Table 1).…”
Section: Therapeutic Response Of Lenvatinib 21 the Ojective Responssupporting
confidence: 86%
“…The PFS in patients with and without high burden of intrahepatic lesion was 3.9 months and 5.3 months, respectively; the difference was not statistically significant [22]. According to a previous study that was reported by Sho et al [20], the ORR and PFS were not signficantly differed between the patients who met the REFLECT criteria and those who did not (61.5%, 10.3 months vs. 48.3%, 9.8 months). They also reported that the ORR and PFS did not differ to a statistically significant extent between patients with an experience of TKI therapy and those without (44.4% 11.1 months vs. 56.9%, 9.1 months), the patients with portal vein invasion at the main portal trunk and those without (40.0%, 5.6 months vs. 54.3%, 9.9 months), or the patients with liver occupation of tumor ≥50% and those without (33.3%, 8.6 months vs. 56.3%, 9.9 months) [20].…”
Section: Efficacy and Safety In Patients Excluded From The Reflect Studymentioning
confidence: 78%
See 3 more Smart Citations